Can Using an Intensive Management Program Improve Primary Care Staff Experiences With Caring for High-Risk Patients? - Meredith, Lisa S. (Fed Pract, 2021)
BACKGROUND: Complex, high-risk patients present challenges for primary care staff. Intensive outpatient management teams aim to serve as a resource for usual primary care to improve care for high-risk patients without adding burden to the primary care staff. Whether such assistance can influence the primary care staff experiences is unknown. The objective of this study was to examine improvement in job satisfaction and intent to stay for primary care staff at the US Department of Veterans Affairs (VA) who sought assistance from an intensive management program. METHODS: Longitudinal analysis of a staff cohort that completed 2 cross-sectional surveys 18 months apart, controlling for outcomes at time 1. Participants included 144 primary care providers at 5 geographically diverse VA health care systems who completed both surveys. Measured outcomes included job satisfaction and intent to stay within primary care at the VA (measured at time 2). Predictors included likelihood of using intensive management teams (measured at time 1). Covariates included outcomes and professional/practice characteristics (measured at time 1). RESULTS: The response rate for primary care staff that completed both surveys was 21%. Staff who indicated at time 1 that they were more likely to use intensive management teams for high-risk patients reported significantly higher satisfaction and intention to stay at VA primary care at time 2 (both P < .05). CONCLUSIONS: A VA primary care workforce might benefit from assistance from intensive management teams for high-risk patients. Additional work is needed to understand the mechanisms by which primary care staff benefit and how to optimize them.